5th European Sports Medicine Congress - Hrazdura, L. (2007)
5th European Sports Medicine Congress will be held in Prague, Czech Republic, October 10-14, 2007. This year, the European Federation of Sports Medicine Associations (EFSMA) marks the 10th anniversary and the vast changes in our profession over the last decade will get their special attention. During the previous congresses, we have repeatedly obtained success in joining the professionals of many liaised branches with our discipline to share their knowledge. The stimulating programme featuring the most actual topics, your participation and naturally the social side of it will support the participants to find new relations and colleagues round Europe.